Children Health Information on Instagram: The Perception of Parents from Y and Z Generation - Arindita, Ruvira; Hasna, Safira; Zahradias (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
This study explores how Gen Y and Gen Z parents engage with children’s health information on Instagram, a popular topic on the platform. Using qualitative methods, researchers conducted in-depth interviews with parents who actively follow health- focused accounts. Findings show that parents’ content perception begins at the selection stage, with most preferring content created by doctors. They favor science-based, easily understood information and are drawn to doctors and influencers who communicate with empathy and clarity. Gen Z parents, typically with younger children, prioritize physical health, while Gen Y parents, often with older children, focus on psychological development. Gen Y is more open to longer text- based content, whereas Gen Z prefers audiovisual formats and still often refers to mom-influencers for children’s health information aside from doctors. The study suggests that health institutions should equip doctors with content creation skills, policymakers should encourage reliance on scientifically backed information, and health educators should personalize messages to connect effectively with each generation. Further studies should explore how fathers perceive health-related information from social media since the parents represented in this article are all mothers.